Positive and Negative Expectations of Hopelessness as Longitudinal Predictors of Depression, Suicidal Ideation, and Suicidal Behavior in High-Risk Adolescents - Horwitz, Adam G. (Suicide Life Threat Behav, 2016)
The relationship between hopelessness and depression in predicting suicide-related outcomes varies based on the anticipation of positive versus negative events. In this prospective study of adolescents at elevated risk for suicide, we used two Beck Hopelessness Scale subscales to assess the impact of positive and negative expectations in predicting depression, suicidal ideation, and suicidal behavior over a 2-4 year period. In multivariate regressions controlling for depression, suicidal ideation, and negative-expectation hopelessness, positive-expectation hopelessness was the only significant predictor of depressive symptoms and suicidal behavior. Clinical interventions may benefit from bolstering positive expectations and building optimism.